Trends in information retrieval: principles and challenges for a new decade of linked data - Méndez, Eva (Anuario ThinkEPI, 2010)
This document shows a state-of-the-art in the information retrieval landscape, with special emphasis on recent trends, strategies and experiences during 2009, as well as research and development expectations in this field for the near future (2010). The paper first gathers a simple review about the growing importance and complexity of Information Retrieval in our discipline, deepening then about the challenge for Librarianship and Information Science for the second decade of 21st century: not only to retrieve information but also to "link data".
Keywords: Information retrieval; Metadata; Semantics; Semantic Web; Web 2.0; Social tagging; Web 3.0; Standards; Linked data; Data portability; New searching strategies